Snack food packaging features and consumer repeat purchase intent - Ng, Kim-Soon; Ahmad, Abd Rahman; Md Yunus, Nur Syafiqah; Ali Hasaballah, Abdel Hafiz (American Scientific Publishers, 2018)
The visual aspects of snack food packaging can influence repeat purchase intention. In today’s busy working lifestyle, snack food may replace one or more of the daily meals. Previous studies reported the inconsistent finding of characteristics of packaging with consumer repeat purchase intent. Thus, this study has been conducted to investigate the relationship between the characteristics of visual and verbal packaging for snacks with consumer repeat purchase intent. The study was conducted at a big supermarket located in the Johore State, Malaysia. The convenient purposive sampling was used to select the consumers who went shopping at the selected supermarket. A total of 217 survey questionnaires were distributed to collect the needed data. Data were analyzed descriptively, the central tendency (skewness), and regression. Overall, the outcome of this research shows the visual features of the snack food packaging is significantly related to consumer repeat purchase intent at p < 0.001. On the other hand, it was found that there is no association between the verbal packaging features with repeat purchase intent. This indicates that visual features are crucial to consumers in their snack food product selection. It is also possible that snacks (junk food) consumers may not be concerned with nutritional value. This could be in the context that such products are of lower involvement, where not much further information is needed. However, recommended that it needs further research in this case. In conclusion, manufacturers can focus on the visual packaging features of snack food product to attract their customers to buy their packed snack food product.